Integrating Green and Gray : Creating Next Generation Infrastructure - Browder, Greg; Ozment, Suzanne; Rehberger Bescos, Irene; Gartner, Todd; Lange, Glenn-Marie (Washington, DC: World Bank and World Resources Institute, 2019)
A new generation of infrastructure projects that harness the power of nature can help achieve development goals, including water security and climate resilience. In this report from the World Bank and World Resources Institute, both organizations are calling for green infrastructure, such as mangroves and wetlands, to play a bigger role in traditional infrastructure planning. Integrating nature into mainstream infrastructure systems can produce lower cost and more resilient services. This report guides developing country service providers and their partners on how to seize this opportunity. It reviews approaches and examples of how to integrate green infrastructure into mainstream project appraisal processes and investments.